Fundamentální a technická analýza vývoje cen zlata - Onykiienko, Marharyta; Fičura, Milan; Pýcha, Mikuláš; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2022)
Precious metals in general, and gold in particular, are one of the popular assets on the financial market. However, a comprehensive understanding of gold prices is still missing. Despite the popularity of trying to find the drivers that could be used for estimating and predicting the price of gold, the available research does not offer a full understanding. This thesis aims to contribute to the discussion on gold prices by identifying potential drivers and by applying a set of econometric models used for predicting futures gold returns. To fulfill this aim, the following models have been estimated: ARIMA, ARIMAX, VAR, and VECM. To compare the results, an opposite approach – technical analysis –was applied. From the set of methods, following the next indicators were used: MACD, RSI, CCI, and Stochastic momentum index. The performance of both approaches was assessed using investment strategy in a comparison with, which will be compared with the random trading. This thesis contributes to the discussion on gold prices by first, examining the importance of selected factors using various econometric methods and second, by comparing two of the common approaches in order to achieve maximum profit
Vedoucí práce: Milan Fičura
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses